Some Effects of the Personal Income Tax - Bradley, Philip D. (Quarterly Journal of Economics, 1943)
Journal Article Some Effects of the Personal Income Tax Get access Philip D. Bradley Philip D. Bradley Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 58, Issue 1, December 1943, Pages 134–140, https://doi.org/10.2307/1885760 Published: 01 December 1943